2021
DOI: 10.9734/jpri/2021/v33i58a34129
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Lactoferrin Inflammatory Role in Type 2 Diabetes Mellitus with Neutrophil Dysfunction

Abstract: Lactoferrin (LF) is a protein that plays important roles in many diseases including diabetes mellitus (DM). DM is one of the most challenging health concerns of the 21st century. At least 30% of the diabetic population is undiagnosed at any one time, so effective and early diagnosis is of critical concern. Several of the body’s chemicals, such as enzymes, electrolytes, and proteins, have been used as biomarkers in the diagnosis of diabetic diseases. Detection of LF is considered an important sign of type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
(101 reference statements)
2
4
0
Order By: Relevance
“…Albumin has found low concentration in diabetic patient according to Mrag et al, in which album is a diagnostic marker has suggested 31 . However, our study showed the low levels of lactoferrin and IgA which is similar to other previous studies [32][33][34] .…”
Section: Discussionsupporting
confidence: 92%
“…Albumin has found low concentration in diabetic patient according to Mrag et al, in which album is a diagnostic marker has suggested 31 . However, our study showed the low levels of lactoferrin and IgA which is similar to other previous studies [32][33][34] .…”
Section: Discussionsupporting
confidence: 92%
“…It can be hypothesized that a failure of the negative regulation of apoptotic process can lead to necrosis of β-cells. We show that Lactotransferrin is more abundant on Type 2 Diabetes Mellitus saliva samples (FC = 5.25) sustaining the assumptions of previous authors [18] that LTF promotes the neutrophil dysfunction in Type 2 Diabetes Mellitus. HSPA5, identified as protector of ER, is less abundant on Type 2 Diabetes Mellitus saliva samples (FC = -2.48), which corroborates the previous assumption.…”
Section: Negative Regulation Of Apoptotic Processessupporting
confidence: 89%
“…Lactotransferrin promotes apoptosis and the elevated levels have been related with neutrophil dysfunction in Type 2 Diabetes Mellitus [18]. In fact, LTF has been suggested as a biomarker to monitor the development or progression of diabetes and its complications [18].…”
Section: Negative Regulation Of Apoptotic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alhalwani conducted a review on the role of neutrophil inflammation in T2D (24). Although the link between T2D and inflammation is well established, few studies have used a reliable biomarker to demonstrate a direct association between T2D and the immune system (25).…”
Section: Introductionmentioning
confidence: 99%